Protecting opinion freedom and its expression in the Islamic government with preventive measures - Seyyed Mohammad Mostafa Hosseini Kashani (Kom: Časopis za Religijske Nauke)
The purpose of the current research is to examine the preventive strategies of the Islamic government in protecting opinion freedom and its expression based on Islamic teachings. The method is descriptive and analytical and its results show that Islam has special measures to prevent situations in line with the protection of freedom of opinion and expression. Situational prevention is one of the common and classic forms of crime prevention that has existed in human societies for a long time and it includes measures that emphasize the root causes of crime to influence the environment and to make the environmental conditions around people healthy, and some, based on Islamic teachings, have interpreted it as Daf' al Munkar (repelling evil) and Sadd Zarayi' (blocking means of committing a prohibited conduct) and they try to reduce the activity of possible criminals with development programs and policies in various ways in order to protect the freedom of opinion and expression. According to Islamic teachings, measures such as banning the publication of false books and its waste, establishing scientific centers and theorizing chairs, forming religious and political parties and the Hisbah institution are proposed in this field in order to reduce possible crimes, which the Islamic government should consider. It is obvious that coercive and criminal measures to protect the freedom of opinion and expression should be used after these measures. Talking about preventive measures does not mean removing criminal measures. Punitive and coercive measures should be taken into consideration as the last solution considered by the Islamic government to protect the freedom of opinion and its expression.